(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the use of information technology and computer systems in the educational process gives students the opportunity not only to use graphic illustrations, increase the speed of information transfer and increase the intensity of understanding, but also develop their intellectual abilities. In the information age, many higher educational institutions of the world conduct large-scale scientific research on information technologies, information and communication technologies and their modeling tools, motivational mechanisms for the development of the competencies of many teachers. The emergence of electronic devices and global telecommunication environments has led to the creation of educational software tools using hypertext, multimedia and hypermedia technologies, virtual systems. The use of such systems has made it possible to digitize many electronic programs, reference books, books and other resources in information storage systems. This article presents analytical data aimed at enriching intellectual educational resources with the help of information technologies based on the principles of openness, the network principle, the principle of control, the principle of adaptation, the principle of computer support and the principles of data collection